She proclaims : our declaration of independence from a man's world - Palmieri, Jennifer (Grand Central Publishing, 2020)
"When Jennifer Palmieri realized that everything in her life had been shaped by men, she wanted to make a change. From work behavior and use of language to wardrobe choices, she decided to follow her own convictions and reject paternalistic expectations. In an era of wage gaps, the Kavanaugh hearings, the #MeToo movement, and a domineering administration, Jennifer found a way to move beyond the bounds of patriarchy and wants to show readers a way out. Where Dear Madam President introduced a blueprint to succeed and the tools to prosper, She Proclaims gives readers the advice they need to to step out of a man's world and into their own. Jennifer believes that every woman has "power to change the world by changing the way she behaves in it." She Proclaims celebrates the accomplishments and history of the women's movement, and it will inspire you to be subversive, courageous, and bold. This book is a Declaration of Independence for women, broken into three types of sections: A preamble that expresses gratitude for the lessons of a man's world. An assertion: the time has come for women to declare their independence from a world not created for them. Each chapter begins with a "whereas" clause and includes advice for combatting the reality of living in a patriarchy. Through personal reflections and stories of other inspirational female leaders, Jennifer shares the key lessons she's learned from her journey to success"--